Analysis of digital data about the preference of audiovisual audiences - Tamayo Sanchez, Vanessa Andrea (2023)
Currently, audiences have a varied catalog through digital platforms that have generated more perceptiveness when consuming content. The objective of this research is to know the audiovisual preference of audiences in Ibero-America according to how they consume content through digital platforms between 2012 and 2021. For this purpose, fourteen papers were selected from the Ebsco and Redalyc databases, where the year, language, free access, and country of origin were considered. The results showed the freedom and autonomy of the audiences when selecting the content to be consumed whenever they want. In addition, streaming platforms are new consumption models that provide users with a wide range of content according to their preferences. The main limitation of the search was the access to articles that, for the most part, presented relevant titles for the research. In conclusion, there are new audiovisual business models that generate new audiences that can adapt and be more perceptive to the audiovisual content they consume.